The Limits of Media Effects: Field Positions and Cultural Change in a Mutual Fund Market - Jonsson, Stefan; Buhr, Helena (Organization Science, 2011)
Our paper examines how field structures moderate the effect of the business press on organizational outcomes. Prior research suggests that the business press shapes organizational outcomes, but the question of how these effects depend on organizations' positions in a field has attracted limited attention. We address this theoretical limitation in an analysis of how mutual funds in Sweden were affected by periods when the business press increased its negative coverage of mutual fund fees. First, we expect that negative coverage influences the way customers evaluate mutual funds. Second, banks have long occupied a dominant position in this market, and we thus expect banks to be less affected by the negative coverage of fees than other mutual fund managers. We find support for our argument in a longitudinal quantitative analysis of financial net flows into mutual funds. The findings indicate the value of contextualizing media effects and considering how field positions moderate the effects of cultural processes.